Dispersion and Thermal Characteristics of Functionalized Nanoparticles in Oilbased Nanofluids - Ee, Ming Fern (Universiti Teknologi PETRONAS, 2016)
Nanofluids have gained great interest among investigators due to its promising outlook on heat transfer enhancement and many potential applications such as cooling processes, drug delivery systems and micro-manufacturing processes. Nanofluids added with nanometer-sized (1-100nm) solid particles of metal, metal oxide or carbon shows improved heat transfer efficiency. Multiple reports on different types of water-based nanofluids have been published. Despite water being used as the base fluid in numerous experimental studies, the low boiling point of water limits industrial applications which require higher temperature operating conditions. A novel approach of introducing oil as base fluids widens the heattransfer applications of nanofluids. However, due to the low thermal conductivity of oil, nanoparticles can be introduced into the fluid such that the thermal conductivity of oil-based nanofluids is expected to be higher than the conventional heat transfer fluids. The agglomeration of nanoparticles due to intermolecular attractive forces disrupts the stability of nanofluids and decreases the overall thermal conductivity of nanofluids.